2005
DOI: 10.1159/000082351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mild Cognitive Impairment in 60- to 64-Year-Old Community-Dwelling Individuals: The Personality and Total Health through Life 60+ Study

Abstract: This epidemiological study aimed at determining the prevalence of mild cognitive impairment (MCI) in 60- to 64-year-old individuals using different diagnostic criteria. Community dwelling individuals (n = 2,551) in the age range of 60–64 years were recruited randomly through the electoral roll. They were screened using the MMSE and a short cognitive battery, and those who screened positive underwent detailed medical and cognitive assessments. Extant MCI-related diagnoses were established by consensus. Predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
4
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 35 publications
3
46
4
2
Order By: Relevance
“…In this study of subjective and objective measures of memory in the elderly population, to evaluate their usefulness as assessed by the EMQ and determining the best factor structure for this purpose, we found that 8.9% of elderly adults had an objective memory deficit, matching literature data reporting a prevalence between about 6% (29,30) and 15% (31). We had recruited our participants by means of a newspaper advertisement for attending a course on aging-related changes of memory, and this method may have induced a bias in sample selection, but as we found the same prevalence of memory deficits as reported in previous studies, we can assume that our sample was representative of the elderly population.…”
Section: Discussionsupporting
confidence: 77%
“…In this study of subjective and objective measures of memory in the elderly population, to evaluate their usefulness as assessed by the EMQ and determining the best factor structure for this purpose, we found that 8.9% of elderly adults had an objective memory deficit, matching literature data reporting a prevalence between about 6% (29,30) and 15% (31). We had recruited our participants by means of a newspaper advertisement for attending a course on aging-related changes of memory, and this method may have induced a bias in sample selection, but as we found the same prevalence of memory deficits as reported in previous studies, we can assume that our sample was representative of the elderly population.…”
Section: Discussionsupporting
confidence: 77%
“…Del total de participantes, un 3.8% cumplía criterios de sospecha de deterioro cognitivo. El nivel de prevalencia se asemejaría a los encontrados en otros estudios internacionales realizados en Estados Unidos (Ganguli et al, 2004) con valores entre 2.9-4 %, en Toscana (Tognoni et al, 2005) con una prevalencia del 4.9% y finalmente en Australia (Kumar et al, 2005) donde encuentran una prevalencia del 3.7% en personas de 60-64 años. Se ha encontrado que en los grupos de mayor nivel educativo y de personas que han ejercido profesiones de tipo no manual, la frecuencia de personas con sospecha de deterioro cognitivo es menor en comparación con aquellos con nivel educativo bajo y medio y con los que tienen o han tenido profesiones manuales.…”
Section: Discussionunclassified
“…The design of the Personality and Total Health (PATH) through Life Study has been described elsewhere [30]. Briefly, participants who were residents of the city of Canberra and the adjacent town of Queanbeyan, Australia, were recruited randomly through the electoral roll to participate in a study interested in the risk and protective factors for common mental disorders, normal aging and dementia.…”
Section: Methodsmentioning
confidence: 99%